Determinants of wind and solar energy system adoption by U.S. farmers: a multilevel modelling approach - Borchers, Allison M; Xiarchos, Irene; Beckman, Jayson (Energy policy, 2014)
This article offers the first national examination of the determinants of adoption of wind and solar energy generation on U.S. farming operations. The inclusion of state policies and characteristics in a multilevel modeling approach distinguishes this study from past research utilizing logit models of technology adoption which focus only on the characteristics of the farm operation. Results suggest the propensity to adopt is higher for livestock operations, larger farms, operators with internet access, organic operations, and newer farmers. The results find state characteristics such as solar resources, per capita income levels, and predominantly democratic voting increasing the odds of farm adoption. This research suggests the relevance of state policy variables in explaining farm level outcomes is limited, although in combination best practice net metering and interconnection policies—policies designed to encourage the development of small scale distributed applications—are shown to increase the likelihood of farm solar and wind adoption. The prevalence of electric cooperatives—which are often not subject to state renewable energy policies and often service farms—is negatively related with the propensity to adopt and suggests that policy design may be a factor.